Behind the Symbols of Dialogue in the Aceh Conflict:"Special Autonomy, Referendum, Independence, or War - Arif Nurdiansyah; Ratu Balqis; Intan Nurazimah (Journal of Health and Multidisciplinary Health Studies, 2026)
This study aims to examine the effectiveness of the dialogue approach as an instrument for resolving the Aceh conflict from 1976 to 2002, and to identify factors that hinder the achievement of sustainable peace. The armed conflict between the Government of the Republic of Indonesia and the Free Aceh Movement (GAM) has lasted for a very long time, leaving a profoundly traumatic impact on all levels of Acehnese society. On the one hand, the people yearn for a peaceful and swift resolution to the conflict. On the other hand, anxiety over the possibility of retaliation, as has repeatedly occurred in the past, continues to haunt their lives. The novelty of this study lies in the descriptive content analysis approach combined with five integrative theoretical frameworks: Galtung's Positive Peace Theory, Rational Choice Theory, the concept of Asymmetric Autonomy, the Trust Deficit Theory, and Local Identity Theory. This approach yields a more comprehensive understanding of why each offered dialogue instrument often ends up being merely symbolic without producing real peace. Future handling of the Aceh conflict needs to be oriented towards honest and objective dialogue, inspired by a sincere moral commitment from both parties, in order to achieve a just and dignified resolution. The people of Aceh have reached a point of exhaustion from the various forms of suffering they have endured. Therefore, peace can only be achieved if all parties to the conflict are willing to sit together within the framework of a constructive and just political compromise.